Unusual Presentation of Follicular Dendritic Cell Sarcoma as a Cystic Neck Swelling - G. Chidananda-Murthy; P. Babu; J. Chandran; G. Raja (Case Reports in Oncological Medicine)
Follicular dendritic cell sarcoma is a very rare neoplasm that most commonly involves cervical lymph nodes and usually presents as a solid mass. Presentation as a cystic neck mass is very rare. Radiological studies and aspiration cytology are often unreliable, and diagnosis is usually made after thorough clinical and pathological examination along with immunohistochemical analysis. In this article, we report a case of a 42-year-old man who presented with right-sided neck swelling of a 2-month duration. Contrast-enhanced CT showed a cystic lesion in the right side of the neck inferomedial to parotid gland located between medial border of sternocleidomastoid muscle and internal jugular vein. Fine needle aspiration cytology was inconclusive. Patient underwent excision biopsy. Histological examination showed a solid-cystic tumor composed of spindle cells arranged in storiform pattern and showed a positive staining for CD23, CD35, and CD21 that confirmed the diagnosis of follicular dendritic cell sarcoma.